Describing viewpoints on human‐nature relationships to unveil socio‐environmental conflicts and support community‐based projects - Beatriz Demasi; Nina Garcia de Almeida Prado; Flávia Pereira Lima; Charbel N. El‐Hani; Renata Pardini (People and Nature)
Abstract Socio‐environmental changes are threatening Indigenous peoples and local communities (IP&LC), hampering conservation efforts, jeopardizing biocultural diversity and escalating environmental injustice. This situation fostered both collaborative research projects showing the potential of engaging with IP&LC for conserving biocultural diversity, and ideas in sustainability science as the relevance of accounting for plural human‐nature relationships and nature values in decision making. The success of these initiatives, however, depends on unveiling socio‐environmental conflicts as a first step to dialogue and cooperation. We developed a tool to describe viewpoints on human‐nature relationships that underpin socio‐environmental conflicts based on a multicultural conceptual framework and Q‐methodology. To investigate its usefulness to unveil conflicts within community‐based projects, we applied it to community members and researchers working collaboratively in an artisanal fishing community in Brazil. By purposefully choosing 23 participants who ordered 44 statements producing distributions later analysed for correlations, we described three viewpoints on human‐nature relationships and, from them, the main socio‐environmental conflicts within the community. Two viewpoints associated with community members revealed contrasting standpoints about nature resulting from complex transformations—from resource‐dependent to tourism‐dependent—in the community. While some people whose occupations depend on outsiders wish to exploit and earn money with nature, others who depend exclusively on fishing fear that nature is under threat. These viewpoints allowed characterizing divergences that can limit collective organization within the community as well as shared desires for the future. One viewpoint was associated with researchers, highlighting differences between theirs and community members' conceptions. Although framed to a specific situation, given its replicable development and amplitude of its conceptual basis, the tool can be adapted to different contexts. By underscoring the diversity within local communities, our tool helps leaving behind idealized notions about them. It also facilitates reflexivity among researchers on how their viewpoints can impact their relationship with communities. As a way of collectively reflecting about local perspectives on human‐nature relationships, the tool facilitates collaboration and finding ways forward. Read the free Plain Language Summary for this article on the Journal blog.